Scientists and Journalists and Communicating Uncertainty: Collaborating With Sharon Dunwoody. Issue 1 (February 2023) - Friedman, Sharon M.; Rogers, Carol L.
This commentary honors Sharon Dunwoody's scholarship and collaboration by focusing on two co-edited books on science communication. It explores the development of these two seminal publications that influenced the early development of the science communication field. In addition to placing the books in their respective time periods, the commentary highlights Dunwoody's specific contributions as described by her two co-editors and long-time collaborators.